2016
DOI: 10.1055/s-0041-107765
|View full text |Cite
|
Sign up to set email alerts
|

Color Tissue Doppler to Analyze Fetal Cardiac Time Intervals: Normal Values and Influence of Sample Gate Size

Abstract: Isovolumetric time intervals can be analyzed precisely and relatively independent of ROI size. In the near future, automatic time interval measurement using ultrasound systems will be feasible and the analysis of fetal myocardial function can become part of the clinical routine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…However, global LPSS acquired with 15-25 fpc in patient data was not significantly different from a reference group acquired with 46-65 fpc. [36][37][38] The main strength of speckle tracking is the assessment of displacement and strain analysis. In this study, we could achieve global and segmental LPSS values with high intra-and inter-observer correlations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, global LPSS acquired with 15-25 fpc in patient data was not significantly different from a reference group acquired with 46-65 fpc. [36][37][38] The main strength of speckle tracking is the assessment of displacement and strain analysis. In this study, we could achieve global and segmental LPSS values with high intra-and inter-observer correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in the field of TDI for proper acquisition of tissue velocities and the short duration of myocardial tissue movements, high frame rates are required in order to obtain an adequate temporal resolution. [36][37][38] The main strength of speckle tracking is the assessment of displacement and strain analysis. Because of a lower heart rate, temporal resolution in adult echocardiography is higher than in fetal application and cardiac timing might be more reliable than in the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…cTDI does not differentiate between active motion and passive motion; thus, fetal or maternal movements may cause artefacts. Velocity measurements are, furthermore, influenced by angle of insonation and the size of the used region-of-interest (ROI) [19,20]. The applicability of the use of velocities in fetuses is, therefore, limited.…”
Section: Introductionmentioning
confidence: 99%
“…F I G U R E 6 Scatter plot displaying intrarater reliability of rater 1 with repetitive assessment of left ventricular global AFR-based LPSS in 20 randomly selected fetuses for assessment of intraclass correlation coefficient (LV = left ventricle; AFR = acoustic frame rate; LPSS = longitudinal peak systolic strain) Further, it was concluded that, in contrast to previous publications on tissue Doppler imaging (TDI) derived strain and strain rate, high FR 35 (>100 Hz) do not seem to be needed for the assessment of peak longitudinal, circumferential, or radial 2D-strains. [36][37][38] As we recently demonstrated, biventricular global LPSS values with high intra-and interobserver correlation can be already acquired with low FR of 30 fps and 60 fps. [36][37][38] As we recently demonstrated, biventricular global LPSS values with high intra-and interobserver correlation can be already acquired with low FR of 30 fps and 60 fps.…”
Section: Dicom Fr-based Global Lpss Data Pairs In a Bland Altman Analmentioning
confidence: 82%
“…28 In particular, in the field of TDI with the need to acquire tissue velocities properly and to overcome short duration of myocardial tissue movements, high FR are required in order to obtain an adequate temporal resolution. [36][37][38] As we recently demonstrated, biventricular global LPSS values with high intra-and interobserver correlation can be already acquired with low FR of 30 fps and 60 fps. 22 When frames were corrected for fetal heart rate, we achieved mean temporal resolutions of 12 fpc (30 fps group) and 25 fpc (60 fps group).…”
Section: Re Sultsmentioning
confidence: 82%